Penggunaan Algoritma Multi Criteria Decision Making dengan Metode Topsis dalam Penempatan Karyawan - Pramudhita, Agung N.; Suyono, Hadi; Yudaningtyas, Erni (Jurnal EECCIS, 2015)
The employees are a major asset in the company so that the company can operate properly. In employees pacement, often a mismatch between the positions of the competence of employees. As a result, many employees resigned because of the mismatch. MultiCriteria Decision Making (MCDM) algorithms can be used to overcome these problems. This research builds on a Decision Support System (DSS) to assist managers in the process of employees placement . DSS is built by one of the methods contained in MCDM, which is Technique for Order of Preference by Similarity to Ideal Solution (TOPSIS) method. Results from this study indicate TOPSIS method appropriate to be used as a method to determine the ranking of candidates deserves to be placed. This is evidenced by the level of accuracy of up to 85%. While the execution time of methods TOPSIS while given 20 the data only reaches 0.7444 seconds.Keywords: AHP, DSS, MCDM, placement, TOPSIS